(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2025)
697 / 5.000 The text presents an analysis of the changes made to the scripts of MathLibras videos, which aim to create accessible and bilingual teaching material for teaching mathematics to deaf students, with Libras as the first language and Portuguese in the subtitles as the second. The work focused on four videos, which allowed for self-reflection, in which similarities and differences were verified, and how the changes allowed for a greater reach of the project, both in subscribers to the channel and in practical application in the partner school. This analysis supported a new script model, shorter, more direct and focused on practice and solving exercises using everyday objects.